Using biochemical and isotope geochemistry to understand the environmental and public health implications of lead pollution in the lower Guadiana River, Iberia: A freshwater bivalve study - Company, Rui (2020)
Lead is a natural component of aquatic ecosystems with no known biological role and is highly toxic. Its toxicity stems from its ability to mimic biologically important metals and to produce membrane damage through lipid peroxidation (LPO). Most lead poisoning symptoms are thought to occur by interfering with an essential enzyme, delta-aminolevulinic acid dehydratase (ALAD), the activity of which is markedly inhibited by lead. The purpose of this work was to study the levels and effects of lead pollution (responses of ALAD and oxidative stress biomarker LPO) in the freshwater bivalve Corbicula fluminea along the lower Guadiana River (Portugal and Spain); a major river system impacted by historic mining pollution and more recent anthropogenic inputs. The results show that the enzymatic activity of ALAD is negatively correlated with the total Pb concentration of the whole tissue suggesting that ALAD has considerable potential as a biomarker of lead exposure in C. fluminea. To identify the sources of lead to which bivalves have been exposed, high precision (206)Pb/(204)Pb, (207)Pb/(204)Pb, (208)Pb/(204)/Pb ratios for C. fluminea confirm that historical mining activities in the Iberian Pyrite Belt are the dominant source of lead pollution in the lower Guadiana River. The isotope patterns however exhibit marked seasonal and geographic variation in response to rainfall and river water management. Locally, other anthropogenic sources of lead have been detected in C. fluminea close to population centres, thus adding to its versatility as a freshwater bio-indicator. Overall, the study highlights the value of natural ecosystems as monitors of water quality and their importance for public health assessment and surveillance.